2018
DOI: 10.3389/fmicb.2018.01133
|View full text |Cite
|
Sign up to set email alerts
|

Rhizosphere Microbiomes Modulated by Pre-crops Assisted Plants in Defense Against Plant-Parasitic Nematodes

Abstract: Plant-parasitic nematodes cause considerable damage to crop plants. The rhizosphere microbiome can affect invasion and reproductive success of plant-parasitic nematodes, thus affecting plant damage. In this study, we investigated how the transplanted rhizosphere microbiome from different crops affect plant-parasitic nematodes on soybean or tomato, and whether the plant’s own microbiome from the rhizosphere protects it better than the microbiome from fallow soil. Soybean plants growing in sterilized substrate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 38 publications
0
44
2
Order By: Relevance
“…The importance of the rhizosphere microbiome in plant-nematode interactions has been extensively reviewed (Kerry, 2000;Griffiths et al, 2007;Sikora et al, 2007;Nyaku et al, 2017;. Importantly, some recent studies have demonstrated that the transfer of the rhizosphere microbiome from one crop to another significantly alleviated nematode infection and enhanced the plant resistance to PPN (Elhady et al, 2018;Zhou et al, 2019). This effect depended on the plant species.…”
Section: Importance Of the Rhizosphere Microbiota In Plant-nematode Imentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of the rhizosphere microbiome in plant-nematode interactions has been extensively reviewed (Kerry, 2000;Griffiths et al, 2007;Sikora et al, 2007;Nyaku et al, 2017;. Importantly, some recent studies have demonstrated that the transfer of the rhizosphere microbiome from one crop to another significantly alleviated nematode infection and enhanced the plant resistance to PPN (Elhady et al, 2018;Zhou et al, 2019). This effect depended on the plant species.…”
Section: Importance Of the Rhizosphere Microbiota In Plant-nematode Imentioning
confidence: 99%
“…This effect depended on the plant species. The plant's own microbiome protected it better from root invasion of PPN than the bulk soil microbiome or a foreign microbiome, with the notable exception of the highly suppressive maize microbiome (Elhady et al, 2018). Furthermore, Hussain et al (2018) revealed that the same subset of microbial OTU was commonly enriched in the rhizosphere and root endosphere upon nematode challenge in suppressive soil.…”
Section: Importance Of the Rhizosphere Microbiota In Plant-nematode Imentioning
confidence: 99%
“…Root border cells and root exudates play a crucial role in shaping the microbial communities in the rhizosphere, eventually resulting in a positive plant-soil feedback (Bertin et al, 2003;Bais et al, 2006;Doornbos et al, 2012;De-la-Peña and Loyola-Vargas, 2014;Ma et al, 2017). Evidence is accumulating that certain beneficial microorganisms suppress plant-parasitic nematodes by inducing systemic resistance (ISR) in plants (Reitz et al, 2000;Munif et al, 2001;Siddiqui and Shaukat, 2004;Dababat and Sikora, 2007;Adam et al, 2014b;Selim et al, 2014;Martínez-Medina et al, 2017b;Elhady et al, 2018;Kang et al, 2018;Silva et al, 2018;. In the initial phase of microbially induced plant defense the pattern recognition receptors localized on the plant cell membranes recognize molecular structures on the microbe/ pathogen surface that are referred to as microbe/pathogenassociated molecular patterns (MAMP/PAMP) (Jones and Dangl, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the rhizosphere supports a marked proliferation and enrichment of specific microorganisms (Jones et al 2009). Beneficial microorganisms associated with plant roots can play an important role in nutrient uptake and plant growth (Gaiero et al 2013), disease suppression (Peralta et al 2018), reducing damage from pests (Elhady et al 2018), and resilience during periods of stress (Gaudin et al 2015). The advent of molecular techniques has facilitated a more comprehensive investigation of biodiversity and function at the root surface.…”
Section: Crop Rotationmentioning
confidence: 99%